Multifunctionality and Conflicts in 20 mph Zones - Staricco, Luca (TeMA - Journal of Land Use, Mobility and Environment, 2011)
In the field of mobility, conflicts and local opposition may be generated not only by hard implementation of big transport infrastructures, but also by soft measures of traffic regulation. An example is represented by 20 mph Zones, which aim to enhance the intrinsic multifunctionality of urban streets: they try to limit the entity and the speed of car flows in residential areas through re-designing road spaces, so to improve in the meantime the liveableness and the environmental and aesthetic quality of these areas. The speed limitation of 20 mph can however determine protests and disputes by local residents and workers, as it disadvantages private motorized mobility, which represents – at least in most current Italian cities – the main form of mobility. The paper analyzes this kind of conflicts, through the case study of the Mirafiori Nord 20 mph Zone in Turin, which is recognized as a best practice in the Italian context. The analysis of this case, as well as the investigation of the main European and American guidelines on traffic calming techniques and plans, shows that a few critical issues turn out to be crucial in order to prevent and manage these conflicts. First of all, a prompt, well-timed communication plan is essential in order to inform residents and users of the area about the potential costs and benefits of traffic calming measures: even before implementation works begin, people has to know that lower accessibility levels by car will be compensated by an improvement of streets liveableness and environmental quality. From this perspective, residents should be involved in designing the new green and street equipments that may be placed, thanks to the redistribution of significant portions of road space to slow mobility components. Participation of school children is quite recommended, for example in the ideation of vertical signs for the access doors of the zone, in experiencing new pedestrian or cycling home-school journeys, and so on. Parking restrictions are often firmly unaccepted by residents, and should carefully assessed before being proposed. Regular reporting of monitored outcomes of the implemented traffic calming measures (mainly in terms of reduction of maximum speed, of dead or injured persons in road accidents, of pollution and noise local levels etc.) must allow keeping residents conscious of the actual benefits they can enjoy. Last, the implementation of 20 mph Zones must be framed in a more general strategy for urban mobility: push measures (just such as 20 mph Zones) for limiting accessibility levels to private traffic flows have to be counterbalanced by pull measures aimed at potentiating public transport, in order to better balance the modal split; otherwise, congestion on the primary road network could spread consistent traffic flows also inside residential areas, invalidating main benefits of traffic calming measures.